Experimental study on driver’s mental load in hairpin curves of mountainous highway - Chen, Ying; Wang, Xiaohui; Zhang, Xiaobo; Chen, Haiyuan; Du, Zhigang; Xu, Jin (Transport, 2023)
In order to reveal the driving psychological characteristics and influencing factors of drivers under the hairpin curve section, 11 continuous hairpin curves on mountain roads were selected for natural driving test, and the on-board instruments were used to collect the driver’s ElectroCardioGraphy (ECG) under the natural driving habits. Analyse the overall heart rate characteristics, Heart Rate Increase (HRI), Heart Rate Variability (HRV) characteristics of drivers, as well as the relationship between heart rate change and the visual performance of curve corner and slop and curve environment. And compared with the general curve. The results show that: with 180° as the limit, the curve angle of the hairpin curve was divided into 3 types: greater, less or approximate. The 3 types of curve angle have different effects on the driver’s heart rate fluctuations. The overall heart rate distribution can be divided into 2 regions, in which the average heart rate of each driver at the curve, which curve angle ≈ 180°, was higher than the other 2 types of curves. The overall fluctuation range of heart rate in the middle of the curve is at the lowest level in the 3-stage curve segment area. Through the eigenvalue analysis of HRI, it can be seen that the drivers were more susceptible to the external environment when going downhill. When going uphill, the distribution range of the heart rate abnormality value was stable, but the sudden change was obvious. However, during the downhill direction, the overall adjacent heart rate varies greatly, but the abrupt change was small. Take the change trend of the HRI in the curve segment as an indicator, heart rate types were divided into 4 categories, continuous tension, relax gradually, relaxation-tension, and tension-relaxation. The 4 modes have a significant relationship with the difference of curve entrance environment. Compared with the modes shown in general curves, they focus on the modes with greater volatility, while the general curves focus on a more single growth trend.